1992
DOI: 10.2527/1992.7061699x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zeranol implants in ram and wether lambs on performance traits, carcass characteristics, and subprimal cut yields and distribution1

Abstract: In two separate 2 x 2 factorial arrangements, 69 male, crossbred lambs were allotted randomly to the following treatments: 1) nonimplanted (NI) rams, 2) implanted (I) rams, 3) NI wethers, and 4) I wethers. In Trial 1, 36 lambs were allotted to treatment groups at birth (n = 9) and I lambs were implanted with 12 mg of zeranol between 1 and 3 d of age and again at weaning (average age of 62 d). Lambs were slaughtered at three time-constant end points of 78, 93, and 107 d on feed postweaning (average age of 155 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Previous research indicates that FG can be improved by implanting lambs twice with 12 mg of zeranol (Nold et al, 1992), and both FG and ADG can be improved by implanting lambs with 12 mg of zeranol 3 or more times (Hufstedler et al, 1996). Domínguez et al (2010) reported that lambs implanted with 24 mg zeranol had increased FG compared with lambs implanted with 12 mg zeranol or with no implantation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research indicates that FG can be improved by implanting lambs twice with 12 mg of zeranol (Nold et al, 1992), and both FG and ADG can be improved by implanting lambs with 12 mg of zeranol 3 or more times (Hufstedler et al, 1996). Domínguez et al (2010) reported that lambs implanted with 24 mg zeranol had increased FG compared with lambs implanted with 12 mg zeranol or with no implantation.…”
Section: Resultsmentioning
confidence: 99%
“…Such reduction in testicular weight amounted to 38.1 and 47.8% in lambs treated with 12 and 24 mg zeranol, respectively. Similarly, weight of testes was reduced approximately 50% by implanting lambs with 12 mg zeranol ( Field et al, 1993) and Nold ( 1990 ) who reported implanting lambs at birth and again at weaning reduced testicle weight by 25%. Also, decreased testicular weight (Calkins et al, 1986 ), epididymal weight, seminiferous tubule diameter and testosterone ( Calkins et al, 1986;Nold et al, 1992) have been observed in lambs implanted with zeranol post weaning.…”
Section: Testicular Weightmentioning
confidence: 98%
“…Similarly, weight of testes was reduced approximately 50% by implanting lambs with 12 mg zeranol ( Field et al, 1993) and Nold ( 1990 ) who reported implanting lambs at birth and again at weaning reduced testicle weight by 25%. Also, decreased testicular weight (Calkins et al, 1986 ), epididymal weight, seminiferous tubule diameter and testosterone ( Calkins et al, 1986;Nold et al, 1992) have been observed in lambs implanted with zeranol post weaning. It has been suggested that the action of the estradiol implant is mediated through changes in luteinizing hormone secretion (D,Occhio et al, 1984), or by blocking gonadotropin release at the level of hypothalamus .…”
Section: Testicular Weightmentioning
confidence: 98%
See 1 more Smart Citation
“…Factors taken into account in assessing meat and carcass quality in cattle according to USDA standards include carcass weight, carcass length, backfat thickness, longissimus dorsi muscle thickness, pelvic fat percentage, marbling score, and fat color (Nold et al 1992). Ultrasound imaging has been used since 1960 to measure muscle fat thickness in beef cattle which is a parameter in the Quality Beef Contest at the International Livestock Exposition (Stouffer 2004).…”
Section: Introductionmentioning
confidence: 99%